(untitled) (Iranian Journal of Kidney Diseases, 2018)
Introduction. This study aimed to assess the number and profiles of patients initializing peritoneal dialysis form the Henan Peritoneal Dialysis Registry, a provincial database in central China. Materials and Methods. All patients aged 18 years and greater, initializing peritoneal dialysis within the province during 2007 to 2014 were included. Demographic characteristics were collected and clinical parameters included the type of renal diagnosis (primary glomerular, secondary glomerular, and others) and recorded major comorbidities in the neural, cardiovascular, respiratory, gastrointestinal, and endocrine systems. Laboratory measurements at treatment including blood urea nitrogen and creatinine were also determined. Differences, as a temporal trend over the period, were analyzed using a nonparametric test for trend across ordered groups. Results. A total of 2540 patients were included. The number of patients increased rapidly by 8-fold from 2007 (n = 70) to 2014 (n = 592). Overall, 40% were 55 years and older, and 60% were females. Forty-five percent of the patients were diagnosed with primary glomerular disease; 40%, secondary glomerular disease; and 15%, other kidney diseases. Half of the patients had comorbid conditions in cardiovascular system, followed by conditions in of the endocrine (15%) and neural (5%) systems. Over the study period, trends were in favor of more proportions of younger patients, female patients, and patients with secondary glomerular disease. Conclusions. Peritoneal dialysis care increased rapidly in central region of China, with more younger and female patients over the study period.